Entrepreneurial Passion And Social Entrepreneurship Intention: A Mediation Study Self-Efficacy In Sociopreneurs - Subangkit, Wita Wahyuni; Mubarok, Teten Muhamad Sapril (Entrepreneurship Faculty, Universitas Garut, 2025)
This study is intended to examine the relationship between Entrepreneurial passion and Entrepreneurial intention through entrepreneurial self-efficacy. The population of this study are sociopreneur business actors in Indonesia. This type of research is quantitative research with a descriptive approach. The sample used was 100 respondents who were distributed using a questionnaire through the google form media and then processed using the SPSS static 25 and SmartPls 3 applications using simple random sampling. The analysis used in this study is the value of R-Square, Direct Effect and Indirect Effect as well as hypothesis testing using bootstrap methods and T statistics. The purpose of this study is to determine whether there is a relationship between Entrepreneurial passion and Entrepreneurial intention through entrepreneurial self-efficacy. The results of this study state that there is an indirect relationship between Entrepreneurial passion and Entrepreneurial intention through entrepreneurial self-efficacy with the original sample value of 0.351. Entrepreneurial intention variable has a significant effect of 67% on Entrepreneurial passion and another 33% is influenced by variables not mentioned in this study.